Peningkatan Kualitas Pembelajaran Anak Usia Dini melalui Pemanfaatan Lingkungan Sekitar sebagai Sumber Belajar - Miftah Kusuma Dewi (Universitas Islam Tribakti Lirboyo Kediri, 2021)
Early childhood is a period that is often called the golden age to grow and develop accordingto age levels quickly and greatly. In this period, children are educated by providing stimulus, parenting guidance and providing activities that are centered on developing children's abilities and skills. The learning process of early childhood which is fun, interesting and effective for children is influenced by several elements, including the availability of learning resources that can support learning activities. Learning resources in the early childhood learning process have an important role in the success and achievement of expected development. The problem that often arises in educational institutions is the lack of available learning resources. Therefore, teachers are expected to be more creative in utilizing the surrounding environment as a learning resource to improve and mak e learning effective. This topic is important to study because the use of the surrounding environment as a source of learning is one aspect that early childhoo d educators must pay attention to so that learning becomes interesting and effective. This study uses a library research research method or library research. The data in this study are in the form of manuscripts and books, all of which are sourced from librarian treasures. And the results of this study aim that educators and students understand that the surrounding environment as a learning resource provides various things that children can use and learn to add insight and knowledgethat they do not get in the classroom